Stabilization of Black Cotton Soil with Cement, Rice Husk Ash and Granite Tile Powder - Noah, Abuh Adah; Abdulkarim, Ibrahim Ikara; Hassan, Ibrahim; Olubunmi, Adetoye (Journal of Multidisciplinary Research Advancements, 2026)
This investigation examines the efficacy of cement, rice husk ash (RHA) and granite tile powder (GTP) as stabilizing additives for black cotton soil (BCS), with the aim of upgrading its performance as a sub‑base material for roads, runways, and other pavement structures. Given the inherently poor geotechnical characteristics of BCS, a response‑surface methodology employing a central composite design (CCD) was adopted to optimize the RHA–GTP blend for maximal improvement in engineering properties. The study demonstrates that RHA and GTP exert pronounced influence on key parameters: maximum dry density (MDD), optimum moisture content (OMC), unconfined compressive strength (UCS), and California bearing ratio (CBR). Incorporation of 6 % RHA and 4 % GTP reduced MDD from 1.64 Mg m⁻³ to 1.41 Mg m⁻³, a decline attributable to the porous microstructure of the additives which elevates void ratio and lowers bulk density. Conversely, OMC increased from 18.9 % to 27.5 % owing to the high silica content in RHA and GTP that forms a moisture‑retentive gel upon hydration. The CBR response exhibited a non‑linear trend: up to 6 % RHA and 3 % GTP, the unsoaked CBR rose from 13 % to 37 %, signifying enhanced bearing capacity. Numerical optimization via CCD identified an optimal formulation of 5 % RHA and 2 % GTP, yielding OMC = 23 %, MDD = 1.5 Mg m⁻³, UCS = 845 kPa, soaked CBR = 22.5 %, and unsoaked CBR = 32.8 %. These results confirm that tailored RHA–GTP blends can substantially ameliorate the geotechnical performance of BCS, thereby contributing to sustainable and cost‑effective pavement construction. The work concludes with a synthesis of key findings, novel contributions, and recommendations for future research directions.